2018
DOI: 10.3390/toxins10060224
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum Toxin for Central Neuropathic Pain

Abstract: Botulinum toxin (BTX) is widely used to treat muscle spasticity by acting on motor neurons. Recently, studies of the effects of BTX on sensory nerves have been reported and several studies have been conducted to evaluate its effects on peripheral and central neuropathic pain. Central neuropathic pain includes spinal cord injury-related neuropathic pain, post-stroke shoulder pain, multiple sclerosis-related pain, and complex regional pain syndrome. This article reviews the mechanism of central neuropathic pain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 86 publications
3
33
0
6
Order By: Relevance
“…In addition, it was verified that BTX-A could repair the spinal cord injury induced by EMS via reducing apoptosis-related protein expression and increasing the outgrowth of spinal cord nerve cells. This conclusion is consistent with previous research that reported that BTX-A could repair the pain caused by inflammation and neuropathology ( 31 ) and increase the growth of spinal cord axons ( 32 ). Then, the possible mechanism of spinal cord nerve injury repair underlying the analgesic effect was investigating.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, it was verified that BTX-A could repair the spinal cord injury induced by EMS via reducing apoptosis-related protein expression and increasing the outgrowth of spinal cord nerve cells. This conclusion is consistent with previous research that reported that BTX-A could repair the pain caused by inflammation and neuropathology ( 31 ) and increase the growth of spinal cord axons ( 32 ). Then, the possible mechanism of spinal cord nerve injury repair underlying the analgesic effect was investigating.…”
Section: Discussionsupporting
confidence: 93%
“…Dramatic anti-hyperalgesia effects in uninjected contralateral hind paws of the rats were found in this study, which cannot be explained by the peripheral mechanism of BTX-A. These results suggested that BTX-A might have a central effect via the retrograde axonal transport system, which is also presumed to be the mechanism by which BTX-A acts to induce central neuropathic pain [83].…”
Section: Btx Effects In Central Nervous Systemsupporting
confidence: 52%
“…18,19,34,[37][38][39] The effect of BTX-A may also be less evident in patients with no preservation of nociceptive input and structural or functional abnormalities of any one of the different components involved in the BTX-A mechanism of action. We could not identify any predictive factor among either the clinical parameters related to the diabetic neuropathy or the characteristics of selfreported pain severity, CSS, or CTF.…”
Section: Discussionmentioning
confidence: 99%